Fine control of growth and thermotolerance in the plant response to heat stress - Yulong Zhao; Song Liu; Kaifeng Yang; Xiuli Hu; Haifang Jiang (Journal of Integrative Agriculture)
Global warming impacts plant growth and development, which in turn threatens food security. Plants can clearly respond to warm-temperature (such as by thermomorphogenesis) and high-temperature stresses. At the molecular level, many small molecules play crucial roles in balancing growth and defense, and stable high yields can be achieved by fine-tuning the responses to external stimuli. Therefore, it is essential to understand the molecular mechanisms underlying plant growth in response to heat stress and how plants can adjust their biological processes to survive heat stress conditions. In this review, we summarize the heat-responsive genetic networks in plants and crop plants based on recent studies. We focus on how plants sense the elevated temperatures and initiate the cellular and metabolic responses that allow them to adapt to the adverse growing conditions. We also describe the trade-off between plant growth and responses to heat stress. Specifically, we address the regulatory network of plant responses to heat stress, which will facilitate the discovery of novel thermotolerance genes and provide new opportunities for agricultural applications.